SMART CITY VS SMART VILLAGE - Fajrillah Fajrillah; Zarina MohamadV; Wirda Novarika (Jurnal Mantik Penusa)
Currently, research on the theme of smart city and smart village continues to be done.This study aims to determine the comparison of characteristics of smart cities, and smart villages.The benefit of this research is to know the characteristics, what is needed by smart city, and smart village to be able to answer the need for smart city, and smart village.The needs of the city are smart, and the village is smartly different, but there are standards.To create economic balance and economic growth, it is necessary to focus on creating intelligent systems, in order to promote overall economic growth. Keywords: Smart City, Smart Village, Characteristics, Comparison.